Landholder reflections of their engagement in landscape conservation and restoration projects in the Northern Midlands of Tasmania. (30th December 2021) - Bridle, Kerry L.; Foster, Henry; Foster, Simon; Lyne, Crosby; Lyne, Poppy; O'Connor, Roderic; von Bibra, Annabel; von Bibra, Julian; Young, Lindsay; Young, Rae; Davidson, Neil J
Summary: 'Environmentalism without Fanaticism', a sticker on a fridge in a farmer's house, encapsulates attitudes to conservation and restoration over the past 30 years for five farming families in the Northern Midlands. Their willingness to participate in long‐term programmes such as the Tasmania Island Ark project stems from their experience of living in the landscape, their observations of changes in that landscape and their thirst for knowledge to underpin management decisions. Being open to other opinions has led to interactions with 'catalysts', usually researchers and extension officers, who have provided farmers with specific information on the natural values of their landscapes. These interactions—time‐ and context‐specific—have resulted in a working lifetime of involvement in conservation and restoration activities shared between landowners, land‐managers, researchers and the broader community. In this article, we present information shared in interviews with five farming families in the Northern Midlands of Tasmania that explored why and how they have continued to engage with conservation and restoration projects over several decades.